Countercyclical Taxation and Price Dispersion - Eric Mayer; Oliver Grimm (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
In this paper, we explore the benefits from a supply-side oriented fiscal tax policy within the framework of a New Keynesian DSGE model. We show that countercyclical tax rules, which are contingent on the observed welfare gap or alternatively on the markup shock and levied on value added, reduce remarkably the inverse impact of cost push shocks. We state that the tax rule establishes a path for the evolution of marginal cost at the firm level that largely prevents built up of price dispersion. We highlight that this tax policy is also effective under a balancedbudget regime. Hence, fiscal policy can disencumber monetary policy in the light of cost push shocks.
Keywords: E32; E61; E62; 330; Countercyclical fiscal policy; welfare costs; nominal rigidities; Antizyklische Finanzpolitik; Soziale Kosten; Wohlfahrtsanalyse; Preisstreuung; Dynamisches Gleichgewicht; Neoklassische Synthese; Theorie